A criminal's confession: comparing rival ethics in crime and punishment (F. Dostoevsky) - Faro, Giorgio (Church, Communication and Culture, 2017)
Dostoevsky and Nietzsche, following different paths, both envisage the Übermensch. Two years before going mad, Nietzsche read some of the great Russian novelist's works. The aim of this essay is to highlight the link in Crime and Punishment between consequentialism (still widespread today) and the theory of the Übermensch, from the personalist perspective of Dostoevsky. His confutation of the Übermensch is not only a consequence of his faith; it also involves natural law and conscience, paradigms shared by everyone, regardless of whether they are believers.